Topographical measurements on atomically flat surfaces at room conditions through scanning tunneling microscope, a didactic insight - Delgado-Jiménez, Lilliana (2019)
One of the great advances in nanotechnology has been the development of the scanning tunneling microscope, a tool that permits the manipulation of atoms and molecules, the study of electron transport in a single atom, and the generation of images with atomic precision in electrically conductive surfaces. In this paper we describe the tunneling microscope, its operation, a calibration methodology, and how to make topographic measurements on flat surfaces with atomic resolution at room conditions. This is done from a didactic point of view, intended to assist new users or researchers unfamiliar with the technique. Depending on the type of measurement and calibration, we used two conductive samples, gold (111) oriented along the crystallographic direction, and highly oriented pyrolytic graphite (HOPG).